Sistem Informasi Pengelolaan Data Aktivitas Penelitian dan PKM Dosen Universitas Wanita Internasional - Muhamad Nawawi; Hendar Rubedo (Jurnal Manajemen Informatika (JAMIKA), 2021)
Not every universities, including the International Women's University, are able to manage data optimally. The objectives of this study are to describe the current research and PKM data management system at International Women University, to build a research and PKM data management system at International Women University, and to conduct testing and implementation of research and PKM data management systems at the International Women University that has been created. The method used is descriptive-action, which first describes the entire system, then analyzes the shortcomings and weaknesses that occur, and then takes action accompanied by solutions to solve it. The system that will be built later is expected to be an enabler in the management of Research and PKM activities for lecturers at the International Women University. In addition, this system is also expected to become an embryo for the creation of other systems so that the International Women University becomes a modern university based on CBIS (Computer Based Information System).